1989
DOI: 10.2535/ofaj1936.65.6_413
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Study on the Lingual Papillae of the Japanese Insectivora

Abstract: The tongue and lingual papillae of the Japanese Insectivora, the Shinto shrew (Sorex caecuiens saevus), the long-clawed shrew (S. unguiculatus), the dsinezumi shrew (Crocidura dsinezumi dsinezumi) and the Japanese water shrew (Chimarrogale himalyica platycephala), were observed by scanning electron microscope. The tongue of these animals had two vallate papillae. In two species of the Sorex a papilla in the vallate papilla was surrounded by two separated trenches, but in the other species it was surrounded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…Rats, mice, and hamsters have one vallate papilla. Rabbits, moles, suncuses (insectivora) (Kobayashi et al, 1989d;Miyata et al, 1990) Pigs are exceptional among the numerous species classified as artiodactyla for having a pair of foliate papillae, unlike most other artiodactyls which have none. Dogs and cats, which are classified as carnivores, do not have any foliate papillae but, they do have several fingerlike protrusions (lateral organs) arranged linealy.…”
Section: Discussionmentioning
confidence: 99%
“…Rats, mice, and hamsters have one vallate papilla. Rabbits, moles, suncuses (insectivora) (Kobayashi et al, 1989d;Miyata et al, 1990) Pigs are exceptional among the numerous species classified as artiodactyla for having a pair of foliate papillae, unlike most other artiodactyls which have none. Dogs and cats, which are classified as carnivores, do not have any foliate papillae but, they do have several fingerlike protrusions (lateral organs) arranged linealy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated morphological diversity among the oral tissues of mammals (Nickel et al., ), particularly with respect to the three‐dimensional structure of the papillae linguales and their connective tissue cores (CTCs) in terrestrial species (Kobayashi et al., , ; Kobayashi, ; Adnyane et al., ; Watanabe et al., ). Following the early macroscopic studies of insectivores by Sonntag (), there have been several detailed morphological investigations into the papillae linguales of the Soricomorpha, for example, Talpidae such as Mogera (Kobayashi et al., ; Miyata et al., ), Talpa (Jackowiak, ) and Dymecodon (Kobayashi et al., ); and Soricidae including Solex , (Kobayashi and Iwasaki, ; Jackowiak et al., ), Suncus (Kobayashi et al., ; Kobayashi and Iwasaki, ), Chimarrogale (Kobayashi and Iwasaki, ) and Crocidura (Kobayashi (), Kobayashi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Following the early macroscopic studies of insectivores by Sonntag (), there have been several detailed morphological investigations into the papillae linguales of the Soricomorpha, for example, Talpidae such as Mogera (Kobayashi et al., ; Miyata et al., ), Talpa (Jackowiak, ) and Dymecodon (Kobayashi et al., ); and Soricidae including Solex , (Kobayashi and Iwasaki, ; Jackowiak et al., ), Suncus (Kobayashi et al., ; Kobayashi and Iwasaki, ), Chimarrogale (Kobayashi and Iwasaki, ) and Crocidura (Kobayashi (), Kobayashi et al. (, ). However, information is lacking for the papillae linguales and for their underlining CTCs of the Japanese shrew‐moles ( Urotrichus) .…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electron microscopical studies of the lingual papillae in rodents have been performed on the rat (Yoshioka et al, 1976), mouse (Yoshioka et al, 1975), golden hamster (Fujita et al, 1982), Chinese hamster (Kobayashi et al , 1983b), old world harvest mouse (Kobayashi et al , 1983a) and Mongolian gerbil (Iwasaki et al , 1984, Kobayashi et al, 1988 etc. In these species, four types of the papillae were distributed in each definite area on the dorsal and lateral surface of the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Sonntag (1920) reported on the morphology of lingual papillae, those were the filiform, fungiform, vallate, and foliate ones, and on those variations and the differences of the number of vallate papillae by species. Despite studie of tongue papillae in Rodentia have been reported by many workers (Tuckermann, 1890; Sonntag, 1924;Kubota and Togawa, 1966;Kobayashi et al, 1983aKobayashi et al, , 1983bKobayashi et al, , 1988, there were few reports of the Sciuridae (Munch, 1896; Tuckermann, 1890), and no scanning electron microscopic study.…”
mentioning
confidence: 99%